P007: Development of provincial recommendations for domestic violence screening in emergency departments and urgent care settings in Alberta. (May 2019) - Arora, N.; Arora, N.; Arinde, F.; Lang, E.; McDonald, S.; Manji, S.; McCracken, L.; McLeod, L.
Abstract : Introduction : Alberta has one of the highest rates of domestic violence (DV) in the country. Emergency departments (EDs) and urgent care centres (UCCs) are significant points of opportunity to screen for DV and intervene. In Alberta, the Calgary Zone began a universal education and direct inquiry program for DV in EDs and UCCs for patients > = 14 years in 2003. The Calgary model is unique in that (a) it provides universal education in addition to screening and (b) screening is truly universal as it includes all age groups and genders. While considering expanding this model provincially, we engaged in the GRADE Adolopment process, to achieve multi-stakeholder consensus on a provincial approach to DV screening, as herewith described.Methods : Using GRADE, we synthesized and rated the quality of evidence on DV screening and presented it to an expert panel of stakeholders from the community, EDs, and Alberta Health Services. There was moderate certainty evidence that screening improved DV identification in antenatal clinics, maternal health services and EDs. There was no evidence of harm and low certainty evidence of improvement in patient-important outcomes. As per Adolopment, the expert panel reviewed the evidence in the context of: a) values and preferences b) benefits and harms, and c) acceptability, feasibility, and resource implications.Results : The panel came to a unanimous decision to conditionally recommend universal screening, i.e., screening all adults above 14 years of age in EDs and UCCs. By conditional, the panel noted that EDs and UCCs must have support resources in place for patients who screen positive to realize the full benefit of screening and avoid harm. The panel deemed universal screening to be a logistically easier recommendation, compared to training healthcare professionals to screen certain subpopulations or assess for specific symptoms associated with DV. The panel noted that despite absence of evidence that screening would impact patient-important outcomes, there was evidence that effective interventions following a positive screen could positively impact these outcomes. The panel stressed the importance of evidence creation in the context of absence of evidence.Conclusion : A GRADE Adolopment process achieved consensus on provincial expansion of an ED-based DV screening program. Moving forward, we plan to gather evidence on patient-important outcomes and understudied subpopulations (i.e. men and the elderly).